2014
DOI: 10.1001/jamaophthalmol.2013.6222
|View full text |Cite
|
Sign up to set email alerts
|

Graft Adhesion in Descemet Membrane Endothelial Keratoplasty Dependent on Size of Removal of Host’s Descemet Membrane

Abstract: that reviewed the medical records of 200 consecutive patients undergoing DMEK. Fifty-three eyes of 51 patients undergoing DMEK for Fuchs endothelial dystrophy fulfilling the inclusion criteria were enrolled in this study. Based on intraoperative drawings, postoperative slitlamp examination, and photographs, eyes were divided into 2 groups. The diameter of the descemetorhexis was approximately 10 mm in group A (30 eyes), resulting in a peripheral 1-mm zone of denuded stroma between the graft and the host's Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 24 publications
5
40
2
3
Order By: Relevance
“…In any case, we thought that this difference in size would allow a better attachment rate, as has also been recently suggested by the Kruse group [85] .…”
Section: Comments About the Descemet Membrane Endothelial Keratoplastsupporting
confidence: 59%
“…In any case, we thought that this difference in size would allow a better attachment rate, as has also been recently suggested by the Kruse group [85] .…”
Section: Comments About the Descemet Membrane Endothelial Keratoplastsupporting
confidence: 59%
“…In contrast, an 80% air bubble will cover 100% of the graft in a supine and approximately 90% in an upright position. According to Tourtas et al, 23 the higher frequency of graft detachments in the inferior portion of the cornea might be attributed to this part being less in contact with the shrinking air bubble in upright positions of the patients.…”
Section: Discussionmentioning
confidence: 93%
“…In another study, we recently found that the size of the descemetorhexis also has an influence on graft adherence. 23 Other known significant factors include preexisting graft damage, 27 intraoperative trauma, 27 and, as mentioned before, surgeon experience. 28,29 According to our clinical experience, the amount of intraoperative rolling and the ease of graft insertion and its fragility all depend on donor age.…”
Section: Discussionmentioning
confidence: 98%
“…14,24-26 These techniques include elimination of viscoelastic, use of SF6, and oversizing the descemetorrhexis of the recipients. 3,7,26,27 Often, a combination of surgical techniques to efficiently unfold the DM scroll is necessary, particularly in eyes with altered anatomy, such as those that have undergone previous glaucoma surgeries.…”
Section: The Current Study Shows That Clinical Outcomesmentioning
confidence: 99%